The estimation method of the unit volume elastic deformation influence on the value of preliminary displacement - Кирилков, В.А. (Problems of Tribology, 2014)
The method, which allows taking into account the contribution of volume elastic deformations of the experimental unit (triborelaxator) into measured complete preliminary displacement, is described. The dependence between contact preliminary displacement and complete preliminary displacement, which is registered during experiments, is given.